Shadow Economy and Loss of Potential Taxes in Indonesia: Empirical Study 1990-2018 - Indupurnahayu, Indupurnahayu; Walujadi, Dedi (Opción, 2019)
The presence of a shadow economy may not be a bad thing for an economy that continues to run dynamically, but it will result in a large loss of state income and also a serious violation of labor regulations. This study aims to ex- amine the shadow economy in Indonesia and the potential loss of tax revenue using the Money Demand Approach, based on empirical data from 1990-2018. The measurement of the shadow economy is carried out in two stages: first, estimation using the econometric model of the aggregate equation for mon- ey demand. Second, calculate the value of the shadow economy through the quantity theory of money transactions, and the potential for tax loss. The key variables used in this study are currency as total money outside the banking system, gross domestic income (GDP) deflator, 6-month deposit interest rate, annual inflation rate, tax to GDP ratio, and M2 ( broad money). The results showed an average of the shadow economy in the 1990-2018 period was 5.44 percent, and the highest in 1998 was 21.75 percent. Tax losses caused by the economic shadow are on average 0.70 percent of GDP.